PENGARUH KONSENTRASI AMILUM JAGUNG PREGELATINASI SEBAGAI BAHAN PENGHANCUR TERHADAP SIFAT FISIK TABLET VITAMIN E UNTUK ANJING - Mariyani, Komang Ayu; Arisanti, Cok. Istri Sri; Setyawan, Eka Indra (Jurnal Farmasi Udayana, 2013)
Corn starch is widely used as excipient in the manufacture of tablets. Native corn starch that have a bad flowability were modificated into pregelatinized corn starch to increase it flowability. The aim of this research was to know the effect of the use of pregelatinized corn starch as disintegrant on the physical properties of Vitamin E tablets for dogs with direct compression method. Pregelatinized corn starch is made by heating the suspenssion of starch at 550 C for 10 minutes and then dried. Pregelatinized corn starch is used as a disintegrants of vitamin E tablets for dog which made by direct compression with three variation of pregelatinized corn starch concentration, that is 5%; 7.5%; and 10%. Quality of resulting tablet are known through the hardness test, friability test, and disintegrating time test. The result from the research will be analysed by One-way ANOVA method. The result showed that the use of pregelatinized corn starch as disintegrant at concentration 5%; 7.5%; and 10% with direct compression method do not give an effect to physical properties of the tablets and  do not meet the requirements of a good tablet.
Keywords: corn starch, pregelatinized starch, disintegrant